Clinical characteristics and in silico analysis of congenital pseudarthrosis of the tibia combined with neurofibromatosis type 1 caused by a novel NF1 mutation - Xu, Jingfang; Zhang, Ying; Zhu, Kun; Li, Jiabin; Guan, Yuelin; He, Xinyu; Jin, Xuejing; Bai, Guannan; Hu, Lidan (Frontiers in Genetics, 2022)
Congenital pseudarthrosis of the tibia (CPT) is a rare congenital bone malformation, which has a strong relationship with Neurofibromatosis type 1 (NF1). NF1 is an autosomal dominant disease leading to multisystem disorders. Here, we presented the genotypic and phenotypic characteristics of one unique case of a five-generation Chinese family. The proband was CPT accompanied with NF1 due to NF1 mutation. The proband developed severe early-onset CPT combined with NF1 after birth. Appearance photos and X-ray images of the left limb of the proband showed significant bone malformation. Slit-lamp examination showed Lisch nodules in both eyes of the proband. Whole-exome sequencing (WES) and Sanger sequencing confirmed the truncation variant of NF1 (c.871G>T, p. E291*). Sequence conservative and evolutionary conservation analysis indicated that the novel mutation (p.E291*) was highly conserved. The truncated mutation led to the loss of functional domains, including CSRD, GRD, TBD, SEC14-PH, CTD, and NLS. It may explain why the mutation led to a severe clinical feature. Our report expands the genotypic spectrum of NF1 mutations and the phenotypic spectrum of CPT combined with NF1.